Integration of physiological and transcriptomic analyses regarding the effects of exogenous salicylic acid on drought resistance in Cinnamomum camphora - Zhao, Tangjie; Guan, Xin; Guo, Huanxian; Peng, Chengbo; Wang, Heng; Zhou, Yunbin; He, Tingwen; Yu, Siting; Gao, Zhu; Zheng, Yuan (Frontiers in Plant Science, 2025)
Salicylic acid (SA) serves as an intercellular signaling molecule, playing a crucial role in plant growth and development, along with the response to environmental stressors. However, molecular regulations that govern salicylic acid-induced resistance to drought in plants remain incompletely elucidated. This research utilized two-year-old C. camphora seedlings as the experimental subjects, employing a two-factor experimental design that incorporated soil moisture×salicylic acid spraying. Through a combination of physiological and transcriptomic analyses, it aimed to elucidate the mechanisms by which exogenous salicylic acid influences the growth and physiological traits of C. camphora seedlings subjected to drought stress, as well as the regulation of salicylic acid-mediated drought-related signaling pathways. Research indicates that SA can markedly improve the substance called chlorophyll fluorescence parameters (that is, Fv/Fm and PIabs) of C. camphora subjected to drought stress, augment photosystem activity during mild drought conditions, and mitigate the damage inflicted by excessive light energy in photosynthetic institutions. SA significantly alleviated oxidative stress in C. camphora seedlings under drought stress by reducing O2- and H2O2 contents and enhancing SOD, POD, and CAT activities. Transcriptome analysis revealed that SA induces DEGs associated with drought resistance. It activates transcription factors that are attached as NAC, bHLH, ERF, and MYB, and regulates genes involved in plant hormone signaling, such as AUX/IAA, PYR/PYL, A-ARRs, and B-ARRs. Additionally, it suppresses the degradation of starch, enhances the expression of genes associated with photosynthesis, and alleviates the adverse effects during conditions of drought that negatively impact the photosynthetic performance of C. camphora, thus enhancing their resilience to drought conditions. Furthermore, SA significantly affected phenylpropanoid synthesis-related genes (such as CcHCT, CcPOD, and CcCOMT). This research seeks to improve understanding of the mechanisms by which SA influences drought tolerance in plants, providing novel insights into enhancing drought resistance in C. camphora.